2019
DOI: 10.1093/brain/awz016
|View full text |Cite
|
Sign up to set email alerts
|

Type I interferon protects neurons from prions inin vivomodels

Abstract: Using cell culture and animal models of prion diseases, Ishibashi et al. show that type I interferon signalling interferes with prion infection in mammals. A selective type I interferon receptor agonist inhibits prion invasion and prolongs survival of prion-infected mice, suggesting potential clinical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…Conversely, data from another series of studies have proposed that type I IFN may play a protective role [ 239 , 240 ]. In contrast to data above [ 235 ], prion disease developed earlier in Ifnar1 −/− mice infected with 22L scrapie prions, whereas treatment with a type I IFN antagonist (RO8191) extended survival times [ 240 ]. The reasons behind these discrepancies are not immediately apparent, but further studies may help to identify specific type I IFN regulators that influence the rate of development of CNS prion disease in certain individuals.…”
Section: Cns Prion Diseasementioning
confidence: 99%
“…Conversely, data from another series of studies have proposed that type I IFN may play a protective role [ 239 , 240 ]. In contrast to data above [ 235 ], prion disease developed earlier in Ifnar1 −/− mice infected with 22L scrapie prions, whereas treatment with a type I IFN antagonist (RO8191) extended survival times [ 240 ]. The reasons behind these discrepancies are not immediately apparent, but further studies may help to identify specific type I IFN regulators that influence the rate of development of CNS prion disease in certain individuals.…”
Section: Cns Prion Diseasementioning
confidence: 99%
“…These proteins are upstream of I-IFN, which results in a cascade of signals inducing immune response [29]. Moreover, ex vivo experiments in scrapie infected mice have shown that inducing I-IFN via TLR signalling reduces PrP Sc concentration in the model host during the early stages of infection [31]. With these two treatments, prion formation can be slown with pharmacological chaperones and the prion population can be significantly diminished with interferons.…”
Section: Possible Treatments For Prion Diseasesmentioning
confidence: 99%
“…Two types of treatments are incorporated in this biological model. The first one consists of a dose of pharmacological chaperones which prevent prion formation based on in vivo experiments by Gunther et al [32]; the second treatment consists of a dose of interferons that decreases the amount of prions in the brain [31]. Our model is based on two previous mathematical models.…”
Section: Possible Treatments For Prion Diseasesmentioning
confidence: 99%
See 2 more Smart Citations